Cav3.2 T-type calcium channels control acute itch in mice - Gadotti, Vinicius M. (Mol Brain, 2020)
Cav3.2 T-type calcium channels are important mediators of nociceptive signaling, but their roles in the transmission of itch remains poorly understood. Here we report a key involvement of these channels as key modulators of itch/pruritus-related behavior. We compared scratching behavior responses between wild type and Cav3.2 null mice in models of histamine- or chloroquine-induced itch. We also evaluated the effect of the T-type calcium channel blocker DX332 in male and female wild-type mice injected with either histamine or chloroquine. Cav3.2 null mice exhibited decreased scratching responses during both histamine- and chloroquine-induced acute itch. DX332 co-injected with the pruritogens inhibited scratching responses of male and female mice treated with either histamine or chloroquine. Altogether, our data provide strong evidence that Cav3.2 T-type channels exert an important role in modulating histamine-dependent and -independent itch transmission in the primary sensory afferent pathway, and highlight these channels as potential pharmacological targets to treat pruritus.